AN INNOVATIVE APPROACH TO MATHEMATICS EDUCATION (American Journal of Technology and Applied Sciences, 2022)
Nowadays, improving the quality of education, students' deep mastery of mathematics and natural sciences has become the main task in our Republic. In order to increase students' interest in mathematics, it is necessary to increase their knowledge first. In order to increase students' knowledge, it is necessary to pay great attention to independent work and creative thinking of students in mathematics classes.